Melanoma secretion of transforming growth factor‐β2 leads to loss of epidermal AMBRA1 threatening epidermal integrity and facilitating tumour ulceration. (1st April 2022) - Cosgarea, I.; McConnell, A.T.; Ewen, T.; Tang, D.; Hill, D.S.; Anagnostou, M.; Elias, M.; Ellis, R.A.; Murray, A.; Spender, L.C.; Giglio, P.; Gagliardi, M.; et al.
Summary: Background: For patients with early American Joint Committee on Cancer (AJCC)‐stage melanoma the combined loss of the autophagy regulatory protein AMBRA1 and the terminal differentiation marker loricrin in the peritumoral epidermis is associated with a significantly increased risk of metastasis. Objectives: The aim of the present study was to evaluate the potential contribution of melanoma paracrine transforming growth factor (TGF)‐β signalling to the loss of AMBRA1 in the epidermis overlying the primary tumour and disruption of epidermal integrity. Methods: Immunohistochemistry was used to analyse AMBRA1 and TGF‐β2 in a cohort of 109 AJCC all‐stage melanomas, and TGF‐β2 and claudin‐1 in a cohort of 30 or 42 AJCC stage I melanomas, respectively, with known AMBRA1 and loricrin (AMLo) expression. Evidence of pre‐ulceration was analysed in a cohort of 42 melanomas, with TGF‐β2 signalling evaluated in primary keratinocytes. Results: Increased tumoral TGF‐β2 was significantly associated with loss of peritumoral AMBRA1 ( P < 0·05), ulceration ( P < 0·001), AMLo high‐risk status ( P < 0·05) and metastasis ( P < 0·01). TGF‐β2 treatment of keratinocytes resulted in downregulation of AMBRA1, loricrin and claudin‐1, while knockdown of AMBRA1 was associated with decreased expression of claudin‐1 and increased proliferation of keratinocytes ( P < 0·05). Importantly, we show loss of AMBRA1 in the peritumoral epidermis was associated with decreased claudin‐1 expression ( P < 0·05), parakeratosis ( P < 0·01) and cleft formation in the dermoepidermal junction ( P < 0·05). Conclusions: Collectively, these data suggest a paracrine mechanism whereby TGF‐β2 causes loss of AMBRA1 overlying high‐risk AJCC early‐stage melanomas and reduced epidermal integrity, thereby facilitating erosion of the epidermis and tumour ulceration.